International Collaboration in Business English Learning: Enhancing Global Communication Skills of Polytechnic Students - Doris Yolanda Saragih; Hengki Mangiring Parulian Simarmata; Erwin Sirait; Roy Syahputera Saragih; Sandi Maiko Sihite (Yayasan Literasi Sains Indonesia, 2025)
This community service project, titled International Collaboration in Business English Learning: Enhancing Global Communication Skills of Polytechnic Students, was conducted by Doris Yolanda Saragih, S.Pd., M.Pd., in collaboration with Pauline De Goeje (Leiden University) and Mart Vogel (Utrecht University). The activity took place at Politeknik Bisnis Indonesia on September 30, 2025, involving 60 students across two interactive sessions. The main objective was to strengthen students’ Business English competence and cross-cultural communication skills in preparation for participation in global business environments. A production-oriented and communicative approach was applied through case discussions, role-play simulations, and digital-based learning to enhance students’ speaking, writing, and negotiation proficiency. The international collaboration component enriched the experience by providing authentic exposure to professional business contexts and global cultural perspectives. The findings revealed that students showed notable improvement in confidence, vocabulary mastery, and motivation to use English for professional communication. Furthermore, the project contributed to developing employability and intercultural awareness, supporting the institution’s mission to produce globally competitive graduates. Overall, this community service initiative demonstrated that sustainable collaboration with international experts can significantly enhance Business English learning outcomes and prepare students to communicate effectively in global business settings.